Preparation Technology of Ultra-Fine Tungsten Carbide Powders: An Overview - Wu, Yu-Cheng; Yang, Yu; Tan, Xiao-Yue; Luo, Laima; Zan, Xiang; Zhu, Xiao-Yong; Xu, Qiu; Cheng, Ji-Gui (Frontiers in Materials, 2020)
Ultra-fine tungsten carbide (WC) powder refers to WC powders with a particle size between 100 to 500 nm. Researchers have improved the comprehensive properties of WC-based cemented carbides by preparing ultra-fine WC powders. Because of the preparation and application of nano-scale WC powders, ultrafine-grain cemented carbides with excellent hardness and wear resistance have been successfully produced. In this paper, the preparation methods of ultra-fine WC powder are divided into solid-phase, liquid-phase, and vapor-phase methods according to the state of the raw materials (i.e., the W or C source). The liquid-phase methods could realize the preparation of WC at the temperature between 500 - 800 °C. The purity of WC prepared by vapor-phase method is the highest. The solid-phase reduction carbonization method has potential industrial application.